Clinical validation and comparison of the Comprehensive Complication Index and Clavien-Dindo classification in predicting post-operative outcomes after cytoreductive surgery in advanced ovarian cancer. Issue 2 (8th December 2022) - Kengsakul, Malika; Nieuwenhuyzen-de Boer, Gatske M; Udomkarnjananun, Suwasin; Kerr, Stephen J; van Doorn, Helena C; van Beekhuizen, Heleen J
Abstract : Objective: The Comprehensive Complication Index (CCI) is an instrument used to measure cumulative post-operative complications. Our study aimed to validate the CCI after cytoreductive surgery for primary advanced-stage epithelial ovarian cancer, and to compare its diagnostic performance with the Clavien-Dindo classification. Methods: This prospective cohort study classified post-operative complications according to the Clavien-Dindo classification and the CCI. Logistic regression was used to determine the association between both classifications with intensive care unit admission, prolonged length of hospital stay (defined as stays longer than the 75th percentile of all stays in this study), 30-day readmission, and time to initiating chemotherapy after surgery >42 days. Area under the receiver operating characteristic curves (AUC) were used to assess the discriminative performance of each classification. Results: A total of 300 patients were included in the analysis. Most patients (n=255, 85%) underwent interval cytoreductive surgery. Complete cytoreduction was achieved in 235 (78%) patients. Overall, 30-day post-operative complications classified by the Clavien-Dindo classification occurred in 147 (49%) patients. Severe complications (grade ≥3a) occurred in 51 (17%) patients. Approximately 30% (n=82) had multiple complications. The CCI showed an excellent correlation with the Clavien-Dindo classification ( r =0.906, p<0.001). In comparison with the Clavien-Dindo classification, the proportion of patients classified with severe complications increased from 17% to 30% when stratified with the CCI, and 20% of patients were diagnosed with a CCI score that correlated with a higher Clavien-Dindo classification grade. On regression analysis, both Clavien-Dindo classification and CCI had associations with intensive care unit admission, prolonged length of hospital stay, 30-day readmission, and time to chemotherapy >42 days (all p<0.05). AUC demonstrated that CCI (0.842, 95% CI 0.792 to 0.893) and Clavien-Dindo classification (0.813, 95% CI 0.762 to 0.864, p<0.001) had a good diagnostic performance for prolonged length of hospital stay. Conclusions: Both the Clavien-Dindo classification and CCI showed significant associations with all surgical outcomes. However, the cumulative complications score of the CCI demonstrated a more superior discriminative performance than the Clavien-Dindo classification for prolonged length of hospital stay in advanced-stage epithelial ovarian cancer.